2018
DOI: 10.1016/j.jtho.2018.08.567
|View full text |Cite
|
Sign up to set email alerts
|

P1.01-11 Named Patient Use Program for Afatinib in Advanced NSCLC with Progression on Prior Therapy: Experience from Asian Centers

Abstract: 8.4%. CRT was delivered concurrently in 98% of the patients. Median radiation dose was 61.2Gy (range 39.6-69.6Gy); 89% receiving 60Gy. Radiation technique was (3D) conformal (71.0%) or intensity-modulated radiotherapy (IMRT) (27.1%). The 30-day and 90-day surgical mortality rates were 4.7% and 7.5%, respectively. At a median followup of 30 months (range: 3-186 months), estimated OS and FFR (median/5-year) were 61 months/ 49% and 29 months/ 35%, respectively. On univariate analysis (UVA), age 60 (HR, 1.776; 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No comparative studies were identified, but rather, nine single-arm phase I/II trials (range 11–115 patients) [ 40 , 42 , 43 , 45 – 47 , 49 , 52 , 53 ] two prospective cohort studies (29 and 35 patients) [ 23 , 29 , 39 ], two pooled analyses of clinical trials (21 and 23 patients) [ 21 , 48 ], and 22 retrospective observational studies (range 15–165 patients). Half of the studies (n = 16) reported on subgroups or select cohorts of patients with Exon 20ins from studies with broader study populations, and half were conducted in Asia (n = 14), followed by the US (n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No comparative studies were identified, but rather, nine single-arm phase I/II trials (range 11–115 patients) [ 40 , 42 , 43 , 45 – 47 , 49 , 52 , 53 ] two prospective cohort studies (29 and 35 patients) [ 23 , 29 , 39 ], two pooled analyses of clinical trials (21 and 23 patients) [ 21 , 48 ], and 22 retrospective observational studies (range 15–165 patients). Half of the studies (n = 16) reported on subgroups or select cohorts of patients with Exon 20ins from studies with broader study populations, and half were conducted in Asia (n = 14), followed by the US (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies (reported across 21 publications) reported the clinical efficacy/effectiveness and safety of various subsequent-line treatment regimens in patients with Exon 20ins, but based on very limited sample sizes (range 11–165 patients) [ 10 , 23 , 24 , 29 , 30 , 37 , 39 44 , 45 – 53 ].…”
Section: Resultsmentioning
confidence: 99%